What Do They Actually Probe at LHC? - Kirilyuk, A.P. (Наносистеми, наноматеріали, нанотехнології, 2013)
The existence of the omnipresent Higgs field providing the fundamental origin of elementary particle mass is the main theoretical concept behind the ongoing large-scale experiments at the LHC accelerator. We critically reconsider the properties of this concept of mass, noting that it contains many fundamental deficiencies and hard problems leaving serious doubts about this interpretation, without feasible progress in view. We then present another, dynamic and universal concept of mass avoiding these problems and thus opening a competitive new possibility for the LHC result interpretation. It is based on the unreduced, nonperturbative solution to (arbitrary) manybody interaction problem providing the universal origin of relativistic inertial and gravitational mass in the form of emerging complex (chaotic) dynamics within the properly specified elementary field–particle, thus rigorously completing the double-solution ideas of Louis de Broglie. As practically all other old ‘mysteries’ and new problems of fundamental physics are also naturally resolved within this unified complex-dynamic solution due to its essential mathematical novelty and provable completeness, we propose to consider it as a viable alternative possibility in interpretation of the LHC and other high-energy facilities’ results.